Genetic evidence for amlodipine’s protective role in gastroesophageal reflux disease: A focus on CACNB2 - Zhang, Liuzhao; Chu, Quanwang; Jiang, Shuyue; Shao, Bo (PloS one, 2025)
This study aims to elucidate the causal relationship between genetically predicted amlodipine use and the risk of gastroesophageal reflux disease (GERD) using a bidirectional Mendelian Randomization (MR) approach and to explore the underlying genetic and molecular mechanisms through functional enrichment analysis and the construction of a competing endogenous RNA (ceRNA) network. Publicly available GWAS datasets from the Neale Lab consortium were used, including data on amlodipine (13,693 cases, 323,466 controls) and GERD (14,316 cases, 322,843 controls). Genome-wide significant SNPs were selected as instrumental variables and clustered by linkage disequilibrium. MR analysis was conducted using R software with all five methods. Sensitivity analyses assessed pleiotropy and heterogeneity. Drug target genes were analyzed using GO and KEGG pathways. GeneMANIA was used for network visualization, and a ceRNA network was constructed with Cytoscape. Differential gene expression analysis on GERD-related datasets from GEO validated the findings. The MR analysis indicated a significant negative association between genetically predicted amlodipine use and GERD risk (IVW OR = 0.872, 95% CI = 0.812-0.937, P = 0.0002). Sensitivity analyses confirmed the robustness of these findings, showing no evidence of pleiotropy or heterogeneity. The enrichment analysis identified key biological processes and pathways involving calcium ion transport and signaling. The ceRNA network highlighted core targets such as CACNB2, which were further validated by differential expression analysis intersecting drug target genes with GERD-related gene expression changes. This study provides robust evidence of a protective effect of amlodipine against GERD, supported by genetic and molecular analyses. The findings suggest that calcium channel blockers like amlodipine could be repurposed for GERD treatment. The identification of CACNB2 and other core targets in the ceRNA network offers novel insights into the pathophysiology of GERD and potential therapeutic targets, paving the way for personalized medicine approaches to improve patient outcomes.